2019
DOI: 10.1016/j.fertnstert.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Expression of erythropoietin messenger ribonucleic acid in wild-type MED12 uterine leiomyomas under estrogenic influence: new insights into related growth disparities

Abstract: Objective: To determine factors that impact erythropoietin (EPO) production in leiomyomas. We have previously implicated EPO production in promoting the growth of some leiomyomas. Design: The relationship between EPO messenger RNA (mRNA) expression and MED12 gene mutations or mRNA expression levels of high-mobility group AT-hook (HMGA) 1 and HMGA2 were analyzed. Effects of 10 À8 M 17b-E 2 on EPO mRNA expression were evaluated using leiomyoma cells grown in primary cultures. Setting: Graduate school of medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Patients with MED12 mutations reportedly tend to develop multiple and smaller-sized tumors. In line with this, a recent study (2) demonstrated that leiomyomas without MED12 mutation were comparatively larger in size than those with MED12 mutation. This finding could explain why some uterine leiomyomas present an accelerated growth rate that often provokes patients to undergo medical intervention, whereas others might grow slowly or remain unchanged indefinitely.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Patients with MED12 mutations reportedly tend to develop multiple and smaller-sized tumors. In line with this, a recent study (2) demonstrated that leiomyomas without MED12 mutation were comparatively larger in size than those with MED12 mutation. This finding could explain why some uterine leiomyomas present an accelerated growth rate that often provokes patients to undergo medical intervention, whereas others might grow slowly or remain unchanged indefinitely.…”
supporting
confidence: 52%
“…In the context of uterine leiomyoma, MED12-linked mutations disrupt its direct interaction with components of the CDK8 and results in suppression of E-induced transcription and diminished cell growth (3). Considering that EPO production is regulated by E, the suppression of E-induced transcription, as observed in the study by Asano et al (2) in response to E. These findings provide clarity for why the lack of MED12 mutation is correlated with accelerated growth in certain leiomyomas, in that elevated transcription of EPO is induced by E. Thus, new treatments inhibiting EPO expression might be considered as a therapy to prevent the growth in uterine leiomyomas lacking MED12 mutation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, MED12mutated UL are characterized as vascular-poor and slowgrowing tumors. In this regard, it has been reported that erythropoietin (EPO), an important hormone involved in hematopoietic activity, cell differentiation, apoptosis control, angiogenesis, and/or vasculogenesis, was decreased in MED12-mutated ULs under estrogenic influence (5). Mutations in MED12 result in the disruption of mediator kinase activity and, consequently, alter CDK8 function, resulting in suppression of estrogen-induced transcription and diminished cell growth.…”
mentioning
confidence: 99%
“…Mutations in MED12 result in the disruption of mediator kinase activity and, consequently, alter CDK8 function, resulting in suppression of estrogen-induced transcription and diminished cell growth. Because EPO production is regulated by estrogen, the inhibition of estrogen-induced transcription in MED12-mutated ULs could explain the decreased EPO expression levels in response to estrogen in these ULs, suggesting that it may be the reason why these tumors tend to be generally smaller than leiomyomas without MED12 mutation (5).…”
mentioning
confidence: 99%